Leveraging nurse practitioner capacities to achieve global health for all: COVID‐19 and beyond. (2nd October 2020) - Rosa, W.E.; Fitzgerald, M.; Davis, S.; Farley, J.E.; Khanyola, J.; Kwong, J.; Moreland, P.J.; Rogers, M.; Sibanda, B.; Turale, S.
Abstract : Aim: To argue that nurse practitioners have been under‐utilized generally in the current global health environment, creating barriers to achieving universal health coverage and the Sustainable Development Goals. Background: Nurse practitioners are advanced practice nurses possessing expert knowledge and leadership skills that can be optimized to narrow disparities and ensure access to high‐quality health care globally. Nurses worldwide have been challenged to meet global public health needs in the context of COVID‐19 (SARS‐CoV‐2 virus), and there are early indications that nurse practitioners are being called upon to the full extent of their capabilities in the current pandemic. Sources of evidence: PubMed; Google Scholar; the International Council of Nurses; World Health Organization; United Nations; and the experiences of the authors. Discussion: Several international reports, nursing and health organizations have called for continued investment in and development of nursing to improve mechanisms that promote cost‐effective and universally accessible care. Expanding nurse practitioner scopes of practice across nations will leverage their clinical capacities, policy and advocacy skills, and talents to lead at all levels. Conclusion: Ongoing empirical data and policy change is needed to enable the full scope and strategic utilization of nurse practitioners across healthcare systems and contexts. Implications for nursing practice, and nursing and health policy: Widespread education regarding nurse practitioner capacities for interdisciplinary partners, policymakers and the public is needed. Policies that safely expand their roles are critical. Role titles and remuneration reflective of their scope and service are required to lead, sustain and grow the workforce internationally.